2017
DOI: 10.1007/s10802-017-0371-9
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Association Between Birth Weight and Attention Deficit Hyperactivity Disorder

Abstract: A large body of work has investigated the association between birth weight and ADHD and has resulted in mixed findings with regard to the direction and magnitude of this association. Despite the vast amount of research on this topic, a comprehensive and systematic quantification of the association between birth weight and ADHD has yet to be undertaken. A meta-analysis of 88 unique studies (N = 4,645,482) was conducted to quantify the overall effect size of birth weight on ADHD symptoms. Several variables were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 170 publications
5
58
2
3
Order By: Relevance
“…A recent body of research suggests that lower BW is associated with a variety of diseases of adulthood, including cardiovascular diseases, diabetes, hypertension, and other metabolic disorders (Godfrey & Barker, ). Additionally, low BW has been associated with potential risk for depression and anxiety in adulthood (Van Lieshout et al, ), increased fracture risk (Balasuriya et al, ), and neurodevelopmental difficulties including Attention Deficit Hyperactivity disorder (Momany, Kamradt, & Nikolas, ), among other health‐related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent body of research suggests that lower BW is associated with a variety of diseases of adulthood, including cardiovascular diseases, diabetes, hypertension, and other metabolic disorders (Godfrey & Barker, ). Additionally, low BW has been associated with potential risk for depression and anxiety in adulthood (Van Lieshout et al, ), increased fracture risk (Balasuriya et al, ), and neurodevelopmental difficulties including Attention Deficit Hyperactivity disorder (Momany, Kamradt, & Nikolas, ), among other health‐related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the literature in that we used a large population‐based sample of twins, with consistent findings across multiple ADHD scales and multiple informants. In addition, we found that the effect of birth weight was not moderated by gender, gestational age and low birth weight, which confirms findings from a recent meta‐analysis (Momany et al., 2018). The small MZ estimates found in this study are the rule rather than exception in MZ differences analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Momany et al. (2018) reported a small overall correlation between birth weight and ADHD symptoms ( r  = −.15), with a correlation of r  = −.09 when considering population‐based studies only. This may reflect that the environmental architecture underlying ADHD is just as complex as their genetic architecture, which involves small effects of many genetic variants (Demontis et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations